Modifications in the gills of hill stream Moth catfish, Hara hara (Erethistidae, Siluriformes): A light and scanning electron microscope investigation. (February 2020) - Arunima,; Mistri, Arup; Kumari, Usha; Mittal, Swati; Mittal, Ajay Kumar
Graphical abstract: Highlights: SEM and light microscopy of gills in a hill stream fish Hara hara is described. Microridges on gill epithelial surfaces, unlike in most fishes, are punctate. Mucous goblet cells are of one type and secrete glycoproteins in high amounts. Taste buds, generally absent on the gill filaments, are observed in this fish species. Abstract: Present study reports significant modifications in surface ultrastructure, histological organization, and histochemical localization of glycoproteins (GPs) in the gills of a hill stream catfish, Hara hara . Punctate microridges on free surface of epithelial cells covering gill arches, gill rakers, gill filaments and secondary lamellae are considered to provide adaptive plasticity to gills in relation to the environment inhabited by fish. Short and stout gill rakers are considered to prevent food particles to pass in opercular chamber along with respiratory current that could damage delicate gill filaments. Mucous goblet cells show presence of different classes of glycoproteins. GPs with oxidizable vicinal diols are considered to control acidity of acidic GPs. GPs with carboxyl groups have been implicated with defensive mechanism against microorganisms. GPs with O-sulphate esters are associated to trap and to lubricate food particles for easy swallowing. Taste buds on gill arches and gill rakers function to select palatable food particles. Occurrence of taste buds on the gill filaments is regarded significant adaptation to analyse the chemical nature of water. This study could play a significant role to understand adjustment of gills in the hill stream fish.